Metal Machining-Recent Advances, Applications and Challenges - Silva, Francisco J. G. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Machining remains one of the most important manufacturing processes in the metalworking industry. Studies on this process have investigated the machinability of different materials, the behaviour of tools, chip formation, surface integrity, forces involved, and its economic and environmental sustainability. New materials are constantly being developed, and machining research needs to closely follow these developments. This book examines recent research in the machining field, covering several aspects and presenting very interesting developments in this area of knowledge.